2017
DOI: 10.1111/jop.12611
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the role of brain‐derived neurotrophic factor/tyrosine kinase receptor B signaling in head and neck malignancies

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family of growth factors that was first known as responsible for sustain the growth, function, and plasticity of neural cells. BDNF exerts its effects by binding to the tyrosine kinase receptor B (TrkB). The BDNF/TrkB axis has been reported to be overexpressed in several neurogenic and non-neurogenic tumors. Its higher expression was associated with a poor prognosis to patients affected by different human malignancies, tumor growth, invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…NTRK1 fusions are now known to occur in many other solid tumor types, including lung adenocarcinoma, papillary thyroid carcinoma, secretory breast carcinoma, and glioblastoma (GBM) [ 45 , 46 ]. In addition, evidence indicating that NGF/TrkA, BDNF/TrkB, TrkC, or p75NTR play a role in cancer has rapidly accumulated over the past few years, with most studies showing that neurotrophins and their receptors are expressed in cancer cells and influence experimental tumor growth, cellular survival, proliferation, migration, invasion, neovascularization, metastasis, and treatment resistance in many peripheral solid tumor types including colorectal, breast, small cell and non-small cell lung, cervical, bladder, gallbladder, laryngeal, renal, head and neck, and oral squamous cell cancers [ 3 , 5 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Neurotrophin Signaling In Cancermentioning
confidence: 99%
“…NTRK1 fusions are now known to occur in many other solid tumor types, including lung adenocarcinoma, papillary thyroid carcinoma, secretory breast carcinoma, and glioblastoma (GBM) [ 45 , 46 ]. In addition, evidence indicating that NGF/TrkA, BDNF/TrkB, TrkC, or p75NTR play a role in cancer has rapidly accumulated over the past few years, with most studies showing that neurotrophins and their receptors are expressed in cancer cells and influence experimental tumor growth, cellular survival, proliferation, migration, invasion, neovascularization, metastasis, and treatment resistance in many peripheral solid tumor types including colorectal, breast, small cell and non-small cell lung, cervical, bladder, gallbladder, laryngeal, renal, head and neck, and oral squamous cell cancers [ 3 , 5 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Neurotrophin Signaling In Cancermentioning
confidence: 99%
“…The BDNF/TrkB axis is overexpressed in neurogenic and non-neurogenic tumors, as well, its higher expression was reported to be associated with unfavored prognosis in cancer patients. Mechanistic explanations for this issue are related to tumor growth, invasion, metastasis, epithelial-to-mesenchymal transition, and resistance to chemotherapy [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…PIKC3 gene copy number correlated weakly with TrkB-T1 RNA at r = 0.3 and r = 0.47 in LASC and OSCC cells respectively. Pikc3a is a key component of the AKT pathway which in turn has been shown to be regulated by TrkB proteins [17, 18]. Logistic regression revealed that, in LASC, activating mutations of the PIK3CA gene were associated with high TrkB-T1 expression (odds ratio 0.720; 95% confidence interval, 0.577 to 0.899; p = 0.0037).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In oral, head and neck, ovarian, pancreatic, colon, prostate, and gastric cancers and neuroblastomas, high TRKB protein levels correlate with worse patient outcomes [1018]. Rare mutated versions of the NTRK2 gene, which encode proteins consisting of fusions of the TrkB kinase domain with domains of other signaling proteins, are drivers in a number of cancers [17, 1922]. The intact NTRK2 gene is also a potential oncogene [12, 13, 23].…”
Section: Introductionmentioning
confidence: 99%